IL-1β, the first piece to the puzzle of sepsis-related cognitive impairment? - Zhu, Qing; Wan, Li; Huang, Han; Liao, Zhimin (Frontiers in Neuroscience, 2024)
Sepsis is a leading cause of death resulting from an uncontrolled inflammatory response to an infectious agent. Multiple organ injuries, including brain injuries, are common in sepsis. The underlying mechanism of sepsis-associated encephalopathy (SAE), which is associated with neuroinflammation, is not yet fully understood. Recent studies suggest that the release of interleukin-1β (IL-1β) following activation of microglial cells plays a crucial role in the development of long-lasting neuroinflammation after the initial sepsis episode. This review provides a comprehensive analysis of the recent literature on the molecular signaling pathways involved in microglial cell activation and interleukin-1β release. It also explores the physiological and pathophysiological role of IL-1β in cognitive function, with a particular focus on its contribution to long-lasting neuroinflammation after sepsis. The findings from this review may assist healthcare providers in developing novel interventions against SAE.